Characterizing the dynamics of climate and native desert plants in Qatar - Meshal Abdullah (17746950) (2024)
This study aims to measure changes in climatic factors and their relationship to vegetation growth in Qatar to develop a plant-climate characterization for native desert plants. By analyzing Landsat satellite images from 1985 to 2022 and their relation to rainfall patterns, we found significant impacts of climatic variables on vegetation coverage, particularly after 1990. Increased drought seasons correlated with changes in annual temperature, dew point, and soil temperature. Vegetation growth depended not only on rainfall amount but also on the number of rainfall events and accumulation. Optimal rainfall events per year ranged from 10 to 15, with 70 mm being the threshold for healthy vegetation growth. However, the probability of rainfall events over 80 mm was less than 5%, while low rainfall seasons (1–17 mm) were more likely (90–99% chance). Additionally, vegetation cover varied between protected sites, indicating the complexity of arid lands influenced by factors like topography and soil type. These findings suggest a continued decrease in vegetation coverage, leading to more drought seasons and impacting water and food security. We recommend further research on supplementary irrigation to support native species, understand their seasonal growth stages, and better comprehend soil-plant-water connections and water requirements. This study's findings will also inform strategies for managing water resources in protected areas and help in designing policies aimed at mitigating the impacts of climate change on Qatar's fragile desert ecosystems. Other Information Published in: Journal of Arid Environments License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jaridenv.2024.105274